The dilemma of natural resource dependency in gulf countries. - Aljarallah, Ruba Abdullah (Cranfield University, 2019)
Natural resources (NR) serve as useful inputs and vital raw materials for domestic industries, which stimulate and secure sustained economic growth and development. However, the notion that the richness of NR can be translated into a curse rather than a blessing has long been an overarching topic of research for both academics and policymakers. The wealth of NR has noticeable socioeconomic and political impacts that vary among resource-rich countries. Given the importance of the Gulf Countries and their dependency on income from NR, the present study thoroughly analyzes the socioeconomic and political aspects of NR dependency in Kuwait (KWT), the Kingdom of Saudi Arabia (KSA), and the United Arab Emirates (UAE). Firstly, this study examines the economic aspects of NR dependency by taking per capita GDP (PGDP) and Total Factor Productivity (TFP) as dependent variables. Secondly, this study examines the political aspects of NR dependency by taking institutional quality as the dependent variable. Lastly, the present study examines the social aspects of NR dependency by taking human capital as the dependent variable. This study applies the Autoregressive Distributed Lag (ARDL) model and co-integration technique by using time-series data from 1984 to 2014. The results indicate that, in the long-run, dependency on NR has a positive impact on PGDP in the KSA and the UAE, but the relationship is insignificant in KWT. Then, it is found that NR dependency shows a positive impact on TFP in the KSA and a negative impact in KWT, while the relationship is insignificant in the UAE. The results reveal that, in the long-run, institutional quality deteriorates as a result of NR dependency in KWT, but this relation is insignificant in the KSA and the UAE. The results of co-integration illustrate that NR dependency dampens human capital in the three countries in the long-run.
Keywords: Natural resource rents; resource curse; institutional quality; human capital; total factor productivity; Gulf countries; Kingdom of Saudi Arabia; Kuwait; United Arab Emirates